Respuesta :

Answer:

Final answer is [tex]-112\cdot\sqrt{2}a^5[/tex].

Step-by-step explanation:

Given expression is [tex](a-\sqrt{2})^8[/tex].

Now we need to find the fourth term of the given expression  [tex](a-\sqrt{2})^8[/tex]. So apply the nth term formula using binomial expansion.

exponent n=8

4th term means we use r=4-1=3

x=2, [tex]y=-\sqrt{2}[/tex]

rth term in expansion of [tex](x+y)^n[/tex] is given by formula:

[tex]\frac{n!}{\left(n-r\right)!\cdot r!}x^{\left(n-r\right)}\cdot y^r[/tex]

[tex]=\frac{8!}{\left(8-3\right)!\cdot3!}\cdot a^{\left(8-3\right)}\cdot\left(-\sqrt{2}\right)^3[/tex]

[tex]=\frac{8!}{5!\cdot3!}\cdot a^5\cdot\left(-2\sqrt{2}\right)[/tex]

[tex]=\frac{40320}{120\cdot6}\cdot a^5\cdot\left(-2\sqrt{2}\right)[/tex]

[tex]=56\cdot a^5\cdot\left(-2\sqrt{2}\right)[/tex]

[tex]=-112a^5\cdot\sqrt{2}[/tex]

[tex]=-112\cdot\sqrt{2}a^5[/tex]

Hence final answer is [tex]-112\cdot\sqrt{2}a^5[/tex].

ACCESS MORE